In vivo IL-4 prevents allo-antigen driven CD8(+) CTL development - Via, Charles S. (Clin Immunol, 2017)
IL-4 has been shown to suppress acute graft vs. host disease (GVHD) in irradiated hosts. Here we evaluated whether IL-4 suppresses acute GVHD in the un-irradiated parent-into-F1 GVHD model with relevance to renal allograft rejection. IL-4 completely suppressed CD8 CTL when administered with donor cells however this effect was lost if its administration was delayed 3 days. IL-4 did not inhibit donor CD8+ T cell homing to the host spleen but rather prevented donor CD8+ T cell differentiation into CTLs. Studies with IL-4Rα-deficient donor cells or recipient mice demonstrated that IL-4 effects on the host, rather than, or in addition to IL-4 effects on donor cells, were critical for suppression of CTL. Because IL-4 decreased all splenic dendritic cell populations and increased neutrophil and CD8+ T cells, IL-4 may suppress donor CD8+ CTL by decreasing Ag presentation and/or increasing host myeloid and CD8+ T cell suppression of donor T cells.